A study on Roeslerstammiidae (Lepidoptera) in the Insect Collection of Nankai University (NKU), with descriptions of three new species - Zheng, Meiling; Qi, Mujie; Li, Houhun (Zootaxa, 2020)
The specimens of Roeslerstammiidae deposited in the Insect Collection of Nankai University have been reviewed. A total of five species are involved. Three new species are described from Southwest China, Agriothera quadrativalva sp. nov., A. microtricha sp. nov. and Telethera declivimarginata sp. nov. Agriothera elaeocarpophaga Moriuti, 1978 is recorded from mainland China for the first time. Photographs of adults and genitalia are given, along with a key to Chinese species.